Improvement of activated sludge process using enhanced nonlinear PI controller - Sharatul Izah, Sharatul Izah; Mohd Fua'ad , Rahmat; Norhaliza , Abdul Wahab; M.C, Razali; M.S. , Gaya; Syed Salim , Syed Najib (Springer, 2014)
Wastewater treatment plant is a large-scale system and highly known with the nonlinearity of the parameters, making them a challenge to be controlled. In this paper, enhanced nonlinear PI (EN-PI) controller is developed for activated sludge process where a sector-bounded nonlinear gain with automatic gain adjustment is cascaded to conventional static-gain PI. The importance in controlling the dissolved oxygen concentration and the improvement of nitrogen removal process are discussed. The effectiveness of the proposed EN-PI controller is validated by comparing the performance of local control loops and the activated sludge process to the benchmark PI under three different weathers. The EN-PI controller is effectively applied in improving the performances of the static-gain PI, hence controlling the dynamic natures of the plant. Itwas proved by significant improvement in effluent violations, effluent quality index and energy saving of the Benchmark Simulation Model No.1.